Quantitative proteomics analysis of macrophage-derived lipid rafts reveals induction of autophagy pathway at the early time of Francisella tularensis LVS infection - Härtlova, Anetta; Link, Marek; Balounova, Jana; Benesova, Martina; Resch, Ulrike; Straskova, Adela; Sobol, Margarita; Philimonenko, Anatoly; Hozak, Pavel; Krocova, Zuzana; Gekara, Nelson; Filipp, Dominik; et al. (Journal of proteome research, 2014)
Francisella tularensis is a highly infectious intracellular pathogen that has evolved an efficient strategy to subvert host defense response to survive inside the host. The molecular mechanisms regulating these host-pathogen interactions and especially those that are initiated at the time of the bacterial entry via its attachment to the host plasma membrane likely predetermine the intracellular fate of pathogen. Here, we provide the evidence that infection of macrophages with F. tularensis leads to changes in protein composition of macrophage-derived lipid rafts, isolated as detergent-resistant membranes (DRMs). Using SILAC-based quantitative proteomic approach, we observed the accumulation of autophagic adaptor protein p62 at the early stages of microbe-host cell interaction. We confirmed the colocalization of the p62 with ubiquitinated and LC3-decorated intracellular F. tularensis microbes with its maximum at 1 h postinfection. Furthermore, the infection of p62-knockdown host cells led to the transient increase in the intracellular number of microbes up to 4 h after in vitro infection. Together, these data suggest that the activation of the autophagy pathway in F. tularensis infected macrophages, which impacts the early phase of microbial proliferation, is subsequently circumvented by ongoing infection.
Keywords: membránové mikrodomény; Proteomics; Molecular Sequence Data; molekulární sekvence - údaje; Tularemia; Blotting, Western; zvířata; autofagie; myši; proteomika; Mice; buněčné linie; Amino Acid Sequence; Cell Line; tularemie; Animals; Autophagy; western blotting; Membrane Microdomains; sekvence aminokyselin